Analyzing the Effect of Emerging Pedagogies on Students' Problem-Solving Ability in Mathematics at Secondary Level (Journal of Asian Development Studies, 2025)
The study aimed to analyse the "analysing the effect of emerging pedagogies on students' problem solving ability in Mathematics at secondary level". The main objectives of the study were to investigate the effect of flipped classroom through project-based learning on students' problem solving ability in Mathematics at the secondary level. In this chapter, the results and interpretation of the data were presented, which were collected through questionnaires administered to three respondent groups: 200 students, 100 Secondary School Teachers (SSTs), and 50 Head Teachers, for a total sample size of 350 participants. Finding the effect of flipped classroom through project based learning on the problem-solving ability of the students in Mathematics at the secondary level was the aim of this research. The structured questionnaire consisted of 40 items broken down into 10 headings/indicators that included the areas of integration of flipped classroom model, project-based learning strategies, mathematical problem-solving skills, real-world application of mathematics, use of technology in Math learning, collaboration and peer learning, inquiry and critical thinking, motivation and engagement, teacher support and instruction, and administrative and resource support. These signals were: (1) flipped classroom model incorporation (most respondents 90% agreement (2) project-based learning strategies, 92 % agreement, (3) skills of solving mathematical problems, 93% agreement, (4) real-life application of Math, 92 % agreement. Favour this practice, indicating strong endorsement of "work on Math projects based on real-life problems".